Too good to hire? Capability and inferences about commitment in labor markets - Galperin, R.V. et al (Administrative Science Quarterly)
We examine how signals of a candidate$1 (Bs capability affect perceptions of that person$1 (Bs commitment to an employer. In four experimental studies that use hiring managers as subjects, we test and show that managers perceive highly capable candidates to have lower commitment to the organization than less capable but adequate candidates and, as a result, penalize high-capability candidates in the hiring process. Our results show that managers have concerns about a high-capability candidate$1 (Bs future commitment to the organization because they view highly capable candidates as having lower levels of organizational interest$1 (Bmeaning they care less about the mission and values of the organization and exert a lower level of effort toward those ends$1 (Band because they assume highly capable candidates have more outside job options, increasing their flight risk. Our findings highlight that capability signals do not necessarily afford candidates an advantage in selection, suggesting an upper limit on credentials and other signals of capability in helping candidates get jobs. Our study contributes to research on labor markets, human capital, and credentialing by offering a theory for why and when capability signals can negatively influence job candidate selection decisions. - Reproduced s
Keywords: Hiring, Signaling, Organizational commitment, Credentialing, Labor markets